Friberg Equation to Predict Pediatric Distal Forearm Fracture Remodeling. Issue 6 (July 2019) - Pearce, Stephanie S.; Honeycutt, Michael W.; Cutchen, William A.; Tillman, Mark D.; Nimityongskul, Prasit
Abstract : Background: This study is the first to test Friberg's equation's ( Vt = V 0 [ e (− ßt ) ]) accuracy in predicting the residual angular deformity in pediatric distal forearm fractures. Methods: Angular deformities from distal forearm fractures in 50 children (mean age, 9 y) were retrospectively measured on follow-up radiographs once healed and compared to extrapolated angles at respective follow-up intervals from 2013 to 2015. Results: The predicted and actual angulations from 120 radiographs (mean follow-up, 3mo) showed that the mean predicted angle was similar to the measured angle in the radioulnar plane and only 2 degrees greater than the measured angle in the dorsovolar plane. A strong correlation was observed between predicted and measured angles in both planes. Conclusions: Friberg's equation is a valid tool for predicting remodeling potential in pediatric distal 25% forearm fractures. Level of Evidence: Prognostic Study—Level II.